2015
DOI: 10.1128/jcm.02332-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Subtyping Methods against a Whole-Genome-Sequencing Standard for Salmonella enterica Serotype Enteritidis

Abstract: A retrospective investigation was performed to evaluate whole-genome sequencing as a benchmark for comparing molecular subtyping methods for Salmonella enterica serotype Enteritidis and survey the population structure of commonly encountered S. enterica serotype Enteritidis outbreak isolates in the United States. A total of 52 S. enterica serotype Enteritidis isolates representing 16 major outbreaks and three sporadic cases collected between 2001 and 2012 were sequenced and subjected to subtyping by four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
71
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 40 publications
10
71
0
3
Order By: Relevance
“…In other words, outbreaks attributed to food products that are not consumed locally (at a single restaurant or social event, for example) will go undetected, thus preventing strong laboratory evidence to link human cases to each other and to potential sources. Recent studies have demonstrated the strength of WGS subtyping of outbreaks using hqSNV analysis for several foodborne outbreaks or outbreaks attributed to other serovars of Salmonella (4,10,12,14,21), including the previously problematic clonal S. Enteritidis (13). This study yielded very strong laboratory evidence of genetic relatedness between epidemiologically related isolates where previous conventional laboratory evidence obtained by PFGE and phage type was weak at best.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In other words, outbreaks attributed to food products that are not consumed locally (at a single restaurant or social event, for example) will go undetected, thus preventing strong laboratory evidence to link human cases to each other and to potential sources. Recent studies have demonstrated the strength of WGS subtyping of outbreaks using hqSNV analysis for several foodborne outbreaks or outbreaks attributed to other serovars of Salmonella (4,10,12,14,21), including the previously problematic clonal S. Enteritidis (13). This study yielded very strong laboratory evidence of genetic relatedness between epidemiologically related isolates where previous conventional laboratory evidence obtained by PFGE and phage type was weak at best.…”
Section: Discussionmentioning
confidence: 48%
“…The increasing readiness of WGS technology combined with the widely hypothesized and previously reported high concordance of WGSbased typing approaches with epidemiological data have resulted in the widespread adoption of WGS surveillance and outbreak response by global contemporaries responsible for public health and food safety, and this method is positioned to replace PFGEbased molecular epidemiology of foodborne pathogens (10,(12)(13)(14). This revolution in global disease surveillance has created the urgency for Canadian public health laboratories to apply WGS technology to routine public health activities.…”
mentioning
confidence: 99%
“…The other strains of S. Thompson analyzed had three or more nucleotide variations and the epidemiological information available regarding the cases with these exposures was different. Genome sequencing has proven to be effective in several outbreaks (19)(20)(21)(22)(23). The use of the whole genome sequencing technique provides additional powers of discrimination, beyond serotyping and PFGE, to delimit and investigate an outbreak (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, PFGE, the gold standard subtyping method implemented in all PulseNet laboratories, and MLVA often do not provide the resolution to differentiate between outbreak and sporadic samples in this serovar (2,10,11). In Minnesota, 74% of S. Enteritidis isolates are comprised of three CDC PulseNet PFGE pattern subtypes: JEGX01.0004, JEGX01.0002, and JEGX01.0005.…”
mentioning
confidence: 99%
“…Sequence-based analysis of Salmonella organisms from nextgeneration sequencing data has been used to examine outbreak clusters of Salmonella enterica serovar Montevideo (30)(31)(32) and S. Enteritidis (7,11,29). Outbreak-related organisms in these two highly homologous serovars are distinguished by fewer than 20 pairwise single nucleotide polymorphisms (SNPs) compared to the sequence of a reference strain.…”
mentioning
confidence: 99%